2017
DOI: 10.1007/s00280-017-3371-0
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion of added value by bevacizumab to chemotherapy in patients with unresectable or recurrent small bowel cancer

Abstract: The analysis indicates that combination CT for advanced SBA is associated with modest efficacy and safety, and bevacizumab-containing CT may contribute to favorable outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Moreover, a retrospective study included 21 unresectable or recurrent duodenum cancer patients to explore the value of the combination of chemotherapy with bevacizumab. The median OS of patients who received a bevacizumab-chemotherapy combination therapy was 21.9 months 34 . The predictive role of LDH in primary duodenum adenocarcinoma patients receiving antiangiogenetic therapy needs to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a retrospective study included 21 unresectable or recurrent duodenum cancer patients to explore the value of the combination of chemotherapy with bevacizumab. The median OS of patients who received a bevacizumab-chemotherapy combination therapy was 21.9 months 34 . The predictive role of LDH in primary duodenum adenocarcinoma patients receiving antiangiogenetic therapy needs to be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the interpretation of data should consider the following remarks: small sample of patients included, heterogeneity of the study population (SBA with or without ampullary adenocarcinoma), nature of the study, different chemotherapy protocols (FOLFOX-FOLFIRI-CAPOX-SOX) used with bevacizumab and finally, variability of patients set. [ 7 9 ] Even a lower level of evidence supports the option of an anti-EGFR therapy. In fact, only few patients affected with SBA received cetuximab while none was treated with panitumumab until now.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 retrospective analysis reported that the efficacy of cetuximab-containing chemotherapy for RAS wild-type SBA was inconclusive. 116 Subsequently, a phase II trial published in 2018 showed that panitumumab has no clinically meaningful activity in RAS wild-type SBA 117 ; therefore, cetuximab or panitumumab should not be used for treatment of SBA.…”
Section: Systemic Therapy For Metastatic Diseasementioning
confidence: 99%
“…125 Retrospective analyses have supported these results, reporting favorable outcomes in patients treated with bevacizumab-containing chemotherapy regimens without adding significant toxicity. 116,126 Based on these data, FOLFOX, CAPEOX, or FOLFOXIRI may be given with or without bevacizumab as first-line therapy for advanced SBA.…”
Section: Folfox Capeox or Folfoxiri Plus Bevacizumab As First-line mentioning
confidence: 99%